Social Changes and Adaptation Strategy among Bugis Community in Karimunjawa - Titiek Suliyati; Yety Rochwulaningsih (Diponegoro University, 2019)
This study proofing on the existence of Bugis community who lived in Karimunjawa for a long time. As ethnic migrants, Bugis ethnic community have a strong spiritual value, which is accumulated in their wandering philosophy. The philosophy ofpalettui alemu riolo tejjokamu is believed to bethe driver of their high work ethic and adaptation to the environment. In Karimunjawa, Bugis lives in several places such as in Parang village and the biggest settlement of Bugis ethnic community in Kemujan village. Bugis culture and tradition also color their lives such as tradition related to birth, the rite of transition from childhood to adolescence, marriage, death, and other tradition associated with the commemoration of religious holidays. After a long time interacting with the local community and communities of various ethnicities, they experience social changes related to changes in livelihoods, structures, and forms of the settlement, ideology, education, and so on. In line with the development of the tourism sector in Karimunjawa, Bugis people began to exploit their culture and tradition for the tourism sector such as Bugis houses built on shores for tourist lodging. The problem is that will the influx of tourists affect and erode Bugis culture in Karimunjawa? This article is intended to provide a better understanding of social change and the strategy of preserving Bugis ethnic culture in Karimunjawa. Data collection was performed by observation and field study as well as in-depth interviews. Informant selection was performed randomly to obtain homogeneous and purposive samples in order to find the appropriate informant according to the topic of research and snowball sampling to find an informant who knows the research problems based on the recommendation of other parties.